Immunohistochemical characterization of putative primary afferent (sensory) myenteric neurons in human small intestine - Brehmer, Axel; Croner, Roland; Dimmler, Arno; Papadopoulos, Thomas; Schrödl, Falk; Neuhuber, Winfried (Autonomic Neuroscience-Basic & Clinical, 2004)
Pseudouni- or multiaxonal Dogiel type II neurons are the intrinsic primary afferent (sensory) neurons (IPANs) in the guinea pig small intestine. Our aim was to decipher the chemical code of human myenteric type II neurons and to establish their putative vertical projections, i.e., from the myenteric plexus to the submucosa/mucosa. Additionally, we tried to distinguish them chemically from uniaxonal, dendritic type V neurons displaying, at first glance, similar shapes, i.e., smoothly contoured cell bodies with several long processes. Wholemount preparations of the myenteric plexus were immunohistochemically double or triple stained for neurofilaments (NF) and one or two of the following peptides: calbindin, calretinin (CR), calcitonin gene-related peptide (CGRP), somatostatin (SOM) and substance P (SP). In each triple stained wholemount three counts were conducted: (1) NF-positive pseudouni- or multiaxonal (type II) neurons including their reactivities for the above peptides, (2) uniaxonal or NF-negative neurons displaying coreactivities for the above peptides and (3) NF-reactive type V neurons taking into account their reactivities for the above markers. Additionally, type II neurons, which had an axon leading into (disrupted) interconnecting strands towards the submucosa were counted and somal areas of types II and V neurons were measured. The majority of myenteric type II neurons displayed coreactivities for SOM/CR (89.6%), SOM/SP (86.6%) and SP/CR (81.6%), respectively. A minority of type II neurons was positive for CGRP or calbindin. A small population with type III morphology (uniaxonal, long and slender dendrites) displayed the same coreactivities as type II neurons. In contrast, not one single type V neuron was coreactive for SOM/CR, SOM/SP or SP/CR. Out of 627 type II neurons counted in six wholemounts, 84 type II neurons displayed an axon which could be followed into disrupted interconnecting strands indicating a vertical projection pattern. Somal areas of type II neurons were twice as big as those of type V neurons (904±210 versus 449±110 μm). In conclusion, most human myenteric type II neurons contain SOM, SP and CR. We suggest they are the human IPANs. Type V neurons are both morphologically and chemically distinctly different from type II neurons and may represent descending interneurons. Further studies have to decipher the type-specific chemical code of type II neurons distinguishing them also from type III neurons. © 2004 Elsevier B.V. All rights reserved.
Keywords: Enteric nervous system; Gut; Innervation; Morphometry